Nasal IgE production in allergic rhinitis: Impact of rhinovirus infection. Issue 6 (25th March 2019) - Hamed, Ahmed; Preston, DeVon C; Eschenbacher, Will; Khokhar, Dilawar; Workman, Lisa; Steinke, John W; Heymann, Peter; Lawrence, Monica; Soto‐Quiros, Manuel; Platts‐Mills, Thomas A. E.; Payne, Spencer; Borish, Larry
Summary: Background: Rhinovirus (RV) infections exacerbate asthma in part by enhancing an allergic state, and these exacerbations can be mitigated via administration of anti‐IgE. Objective: We investigated the presence of local IgE production in the nose of allergic and non‐allergic subjects and assessed whether this was enhanced by RV. Methods: Local production of specific IgE was determined by comparing ratios of specific to total IgE concentrations between nasal and serum samples. Our initial studies were performed in subjects presenting to the emergency department for allergic and non‐allergic respiratory complaints. Subsequently, we investigated influences of experimental RV infection on nasal sIgE production in an allergic cohort. Results: We found evidence of local sIgE production to Dermatophagoides pteronyssinus in 30.3% and to Blomia tropicalis in 14.6% of allergic subjects. None of the non‐allergic subjects demonstrated local IgE. Subjects with active RV infection were more than twice as likely to have local sIgE (45% vs 14%), and subjects with local sIgE being produced were 3 times more likely to be having an asthma exacerbation. Experimental RV infection was able to induce local sIgE production. Conclusion: These studies confirm local IgE production in a large subset of allergic subjects and demonstrate that allergic asthmatics with local IgE are more likely to develop an asthma exacerbation when infected with RV. Our RV challenge studies demonstrate that at least some allergic asthmatics can be induced to secrete locally generated IgE in their nasal airway after RV infection.